Attitudes toward COVID-19 Vaccination: Staff and Patient Perspectives at Six Health Facilities in Sierra Leone - Stefanie A. Joseph; Jean Gregory Jerome; Foday Boima; Pierre Ricard Pognon; Donald Fejfar; Yusupha Dibba; Daniel Lavalie; Mohamed Bailor Barrie; Aramide Oteju; Mohamed Sheku; Mariama Mahmoud; Jusu Mattia; et al. (Vaccines, 2023)
Sierra Leone is a West African country with a population of over 8 million. With more than half of Sierra Leone’s population living in rural areas, it is important to understand rural populations’ access to and attitudes toward the COVID-19 vaccine. In November 2021, the rate of vaccination coverage in Sierra Leone was only 7% for one dose and 4% for two doses. Understanding perspectives of health facility staff and patients can help strengthen future vaccine campaigns. We conducted a cross-sectional study, between March 2022 and May 2022, of clinical staff, non-clinical staff, and adult (>18 years) patients/caregivers attending six Ministry of Health and Sanitation (MoHS) facilities supported by Partners In Health, four in the Kono district and two in the Western Urban Area district, the capital of Sierra Leone. We assessed the opportunity to vaccinate, vaccine uptake, and intention to vaccinate. Out of the 2015 participants, 11.4% were clinical staff, 18.8% were non-clinical staff, and 69.8% were patients/caregivers. Less than half of the patients/caregivers had the opportunity to be vaccinated (42%), and 22% of patients/caregivers were fully vaccinated. Among the unvaccinated population, 44% would refuse a vaccine if offered to them at no cost. Lack of access to COVID-19 vaccines and to official education messaging, especially for patients and caregivers, is still an underlying problem in Sierra Leone for vaccine uptake, rather than a lack of willingness to be vaccinated.